Las tecnologías digitales al servicio del diseño universal para el aprendizaje - María de los Milagros Rubio Pulido (Journal of Neuroeducation, 2022)
Technology has uses for a wide range of services, including education, being analyzed by different theoretical models in its application to educational environments. Used from a pedagogical approach, technology must favor the learning of all students based on digital accessibility standards. Accessibility in learning is based on the three principles of UDL (representation, implication and action and expression), principles for which technology provides varied and multiple resources and possible actions, both specifically for each principle and in an integrated way to the three. Technology also allows the design of digital and accessible educational content by configuring parameters alluding to the content itself and its format, with support references to do so and application examples in some educational institutions that have used the UDL approach to design resources. open educational. Given that the use of technology in education also involves associated risks, we must be aware of them in order to avoid them or compensate them in favor of the inclusion of all students.